Review of Arons's - Glenn, Charles L. (Education Policy Analysis Archives, 1998)
Stephen Arons, author of Compelling Belief: The Culture of American Schooling (Amherst: University of Massachusetts Press, 1986), is one of the most articulate and influential critics of the educational Establishment from the secular Left. In his new book, he takes on the Clinton Administration's efforts to establish national outcome standards--Goals 2000--which he describes as "comprehensive, centralizing, and insensitive to the diversity of goals that students, families, and communities bring to education. Through the use of federal grants and state regulations, it aims to bring every school in every school district in every state into conformity with politically prescribed standards of what should be learned by every child" (page 4). Arons warns that "[o]nce accepted by the public, Goals 2000 will change the balance of power in schoolhouses and courtrooms in a way unlikely ever to be undone. That change in schooling will very likely undermine the freedom of intellect and spirit that has been so essential to the American experience" (page 98).